Government Policies In Preventing Early Marriage In Sinjai Selatan District Sinjai Regency - RISKA; Zulkifli Arifin; Rahmawati; Sinta (Program Studi Administrasi Publik, 2025)
This study aims to determine the government's prevention in dealing with early marriage in South Sinjai District, Sinjai Regency. The type of research used is qualitative research, the data sources used are primary and secondary, the number of informants is 3 people. From the results of previous research, it shows that the government's prevention in dealing with early marriage in Sinjai Selatan sub-district, Sinjai district, is classified as optimal and not optimal. society. related to the regulation on early marriage has been going well, but not optimal because of the government's lack of firmness towards people who do early marriage. Internal factors that influence this research are on the basis of their own volition while external factors are influenced by several factors such as the economy, education, or community traditions.